Identification of novel phosphatidic acid binding domain on sphingosine kinase 1 of Arabidopsis thaliana - Pandit, Shatakshi (Plant physiology and biochemistry : PPB, 2018)
Copyright © 2018 Elsevier Masson SAS. All rights reserved.